Palm oil based trimethylolropane esters. - Yunus, Robiah; Ahmadun, Fakhru'l-Razi; Ooi, Tian Lye (2010)

(untitled)
Biodegradable polyol esters derived from branced polyol have been developed for various biodegradable lubricant applications. These fluids have excellent thermal stability, better lubricity, low volatility and resits hydrolysis better than other esters. With proper additive, polyol esters are more oxidatively stable than the other synthetic fluids. As a result of extensive studies, palm oil methyl esters were found to be suitable in synthesis of polyol ester that is suitable for used as lubricant base stock in two-stroke engine lubricant and other biodegradable lubricant applications. Palm oil methyl ester (POME) and palm kernel methyl ester (PKOME) were found suitably used in the transesterification of palm oil methyl esters into trimethylolpropane esters. The pour point for the palm oil based trimethylolpropane esters was found to be at least as low as -35 degree C.